2020
DOI: 10.14336/ad.2019.0920
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis, Features, Functions, and Disease Relationships of a Specific Circular RNA: CDR1as

Abstract: In 2011, Hansen discovered the natural antisense transcript (NAT) of the cerebellar degenerationrelated protein 1 gene (CDR1), and further described CDR1 NAT as a circular RNA (CircRNA). CDR1 antisense RNA (CDR1as), which is the official name of CDR1 NAT, is conserved and extensively expressed in most eutherian mammal brains and other specialized tissues. Further studies have elucidated its biogenesis, features, functions, and relationships with diseases. CDR1as is involved in many disease processes as a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…We would like to emphasize that considering circRNA as exonic depends on the knowledge of the genome and available annotation. The best described example is circRNA ciRS-7/CDR1as [ 31 ]. When this circRNA was characterized, only the protein-coding gene CDR1 was described at this locus [ 32 ], but subsequent studies have shown that the parent gene is a long non-coding RNA located on the opposite strand to CDR1 [ 33 ].…”
Section: What Can We Expect From Tools Dedicated To the Detection mentioning
confidence: 99%
“…We would like to emphasize that considering circRNA as exonic depends on the knowledge of the genome and available annotation. The best described example is circRNA ciRS-7/CDR1as [ 31 ]. When this circRNA was characterized, only the protein-coding gene CDR1 was described at this locus [ 32 ], but subsequent studies have shown that the parent gene is a long non-coding RNA located on the opposite strand to CDR1 [ 33 ].…”
Section: What Can We Expect From Tools Dedicated To the Detection mentioning
confidence: 99%
“…LncRNAs are not the only ncRNAs proposed as AD-associated ceRNAs, as these also include circRNAs. One of the best-studied circRNAs is CDR1as, an antisense circular transcript of the Cerebellar Degeneration-Related protein 1 (CDR1), highly expressed in the brain [ 155 ]. This circRNA appears to stabilize the CDR1 mRNA [ 156 ] and to act as a miR-7 sponge, thereby being also called ciRS-7 [ 81 ].…”
Section: Cerna Network and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The first circRNA studied in pancreatic islet cells was ciRS-7/CDR1as, which acts as a sponge of miR-7, one of the most abundant miRNAs present in β-cells. This circRNA is abundant, largely cytoplasmic, and originates from the antisense of the Cerebellar Degeneration-Related protein 1 gene (CDR1) [ 67 ]. Since it contains about 70 conserved miR-7 binding sites, it is either termed Cdr1as (antisense) or ciRS-7 (Circular RNA Sponge for miR-7) [ 67 ].…”
Section: Circrnas In Pancreatic Islet Cellsmentioning
confidence: 99%
“…This circRNA is abundant, largely cytoplasmic, and originates from the antisense of the Cerebellar Degeneration-Related protein 1 gene (CDR1) [ 67 ]. Since it contains about 70 conserved miR-7 binding sites, it is either termed Cdr1as (antisense) or ciRS-7 (Circular RNA Sponge for miR-7) [ 67 ]. Overexpression of ciRS-7 in murine islet cells was found to increase insulin content and secretion [ 68 ].…”
Section: Circrnas In Pancreatic Islet Cellsmentioning
confidence: 99%